2010
DOI: 10.1016/j.jom.2010.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Operations management, entrepreneurship, and value creation: Emerging opportunities in a cross‐disciplinary context

Abstract: EditorialOperations management, entrepreneurship, and value creation: Emerging opportunities in a cross-disciplinary context a r t i c l e i n f o Keywords:Operations management Entrepreneurship Cross-disciplinary research a b s t r a c t Cross-disciplinary research at the intersection of operations management and entrepreneurship offers the potential to generate new knowledge leading to tangible value for the firm. Likewise, themes such as the reliance on firm-external partnerships, the strong technology and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
65
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(70 citation statements)
references
References 51 publications
5
65
0
Order By: Relevance
“…While their results showed that antecedents to corporate entrepreneurship are not strong predictors of innovation performance, when operations controls attributes are taken into consideration, the effect of the antecedents to corporate entrepreneurship show a more significant influence on innovation performance. Thus, in accordance with the increasing interest of blended analysis across OM and entrepreneurship (Kickul et al, 2011) and calls for examining the contingency view of the traditional manufacturing capability-performance model (Sousa and Voss, 2008), we suggest EO as a possible contingency variable for the manufacturing capability-organizational performance link.…”
Section: Manufacturing Capabilities Organizational Performance and Esupporting
confidence: 62%
See 3 more Smart Citations
“…While their results showed that antecedents to corporate entrepreneurship are not strong predictors of innovation performance, when operations controls attributes are taken into consideration, the effect of the antecedents to corporate entrepreneurship show a more significant influence on innovation performance. Thus, in accordance with the increasing interest of blended analysis across OM and entrepreneurship (Kickul et al, 2011) and calls for examining the contingency view of the traditional manufacturing capability-performance model (Sousa and Voss, 2008), we suggest EO as a possible contingency variable for the manufacturing capability-organizational performance link.…”
Section: Manufacturing Capabilities Organizational Performance and Esupporting
confidence: 62%
“…As noted earlier, there are a number of explicit connections and opportunities for the OM and entrepreneurship literature (Kickul et al, 2011;Joglekar and Levesque, 2013;Krishnan, 2013), and this should certainly be true at the intersection of OM and welldevelop entrepreneurship concepts such as EO (Lumpkin and Dess, 1996). It has been suggested that the development of operational capabilities can be positively affected by entrepreneurial behaviour (Giunipero et al, 2005;Kickul et al, 2011).…”
Section: Manufacturing Capabilities Organizational Performance and Ementioning
confidence: 95%
See 2 more Smart Citations
“…innovative posture, proactiveness, and risk-taking behaviour (Kreiser and Davis, 2012;Rauch et al, 2009). There are a number of explicit connection and opportunities for OM and EO (Kickul et al, 2011;Krishnan, 2013;Phan and Chambers, 2013). Entrepreneurial behaviour is acutely important in that it allows firms to leverage their manufacturing competencies and develop capabilities such as flexibility, agility, quality and efficiency (Handfield et al, 2009;Hsu et al, 2011).…”
Section: Introductionmentioning
confidence: 99%